Seasonal energy reserves of the cold-water coral Desmophyllum dianthus from Comau Fjord, Chile - Beck, Kristina K; Schmidt-Grieb, Gertraud M; Kayser, Antonia S; Wendels, Janine; Kler Lago, Alexandra; Meyer, Stefanie; Laudien, Jürgen; Richter, Claudio; Wall, Marlene (PANGAEA, 2024)
Between September 2016 and August 2017, we conducted year-long reciprocal transplantation experiments using the cold-water coral Desmophyllum dianthus along natural oceanographic horizontal and vertical gradients (vertically: 20 m to 300 m depth and horizontally: head to mouth of fjord) in Comau Fjord to study seasonal changes and the acclimatisation potential of its biochemical composition. Seasonal energy reserves (proteins, carbohydrates and lipids) and the C:N ratio of native and novel (cross-transplanted) corals were measured at six shallow (A-F, 20 m) and one deep station (Ed, 300 m) during autral summer (January), autumn (May) and winter (August).
Keywords: Carbohydrate; C:N; energy reserves; Lipid; protein; Reciprocal Transplant; Seasonality; surface area